List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. (Policy Papers; Policy Paper ;, 2013)
The following table lists the IMF members for which the Article IV consultation or the mandatory financial stability assessment has been delayed by more than 18 months. The delay is counted past the scheduled expected date, plus any applicable grace period.